Voice of the ancient - Cossette, Connilyn (Cossette, Connilyn. King's Men, 2023)
"When a nearby city is attacked, Avidan fights for the newly crowned King Saul. When one of his cousins goes missing during the battle, he searches for him and instead stumbles across Keziah--the daughter of a powerful man. Traveling together, they must rely on each other to stay alive and learn to trust the King of Israel to guide their every step"--